Development of application based health monitoring system using GSM module - Tasniem, Anika; Jamil, Nura; Khan, Tabassum (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.